Neuromuscular electrostimulation vs traditional therapy in the stroke patient with oropharyngeal dysphagia: effects on quality of life - randomized study - Gouveia, Carla (2021)
Oropharyngeal dysphagia (OD) is common after stroke. Its presence submits the patient to clinical instability, which can cause complications such as aspiration pneumonia, dehydration, malnutrition and death. The objective was to compare effectiveness of traditional therapy (TT) with associated NMES versus traditional therapy in the rehabilitation of patients with OD after stroke and the effects on their quality of life (QOL). We have observed that in the EG, there is a trend towards a faster recovery of OD, reaching the level 7 of the FOIS scale about a week before the CG. Regarding QOL, it was possible to observe that the patients of both groups, when recovering from DO improved their QOL and that the EG tends to present better results.